DEVELOPMENT OF DIORAMA MEDIA ON CULTURAL DIVERSITY MATERIALS IN MY COUNTRY ISLAMIC ELEMENTARY SCHOOL - Amir Rusdi; Anita Fitriani; Amir Hamzah; Tutut Handayani; Dian Andesta Bujuri (STAI Ma'had Aly Al-Hikam Malang, 2022)
This study aims to: (1) produce valid integrative thematic diorama learning media, (2) produce practical integrative thematic diorama learning media. The method used is the R&D development method with the ADDIE development model which consists of 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The data collection used is a questionnaire and documentation. Test the validity and practicality of the data using a predetermined formula. The subjects of this study were fourth grade students of MI Al-Ittifaqiah Indralaya with a total of 15 students. Therefore, it can be concluded: (1) Produce valid integrative thematic diorama learning media seen from the validity questionnaire of design experts with a score of 62 with an average result of 85, validation of linguists with a score of 49 with an average result of 81, and material expert validation with a score of 58 with an average result of 96.66. (2) Produce practical integrative thematic diorama learning media as seen from the score of 1,379.82 with an average score of 91.98.